Varieties of social learning in children: Characterizing the development of imitation, goal emulation and affordance learning within subjects and tasks - Subiaul, Francys (Cognitive development, 2023)
Children’s social learning (SL) is characterized by significant variation. Explaining when and why children excel in some SL problems but not others is an unappreciated but significant problem in the developmental sciences. Here, two studies explore different forms of SL in preschoolers (3–6 years) using two tablet-based tasks, Cognitive and Spatial. These tasks involve sequencing items by their identity (e.g., Apple→Boy→Cat) or spatial location (e.g., Top→Bottom→Right). Experiment 1 (n = 189) explored children’s ability to learn different sequences by individual—trial-and-error—learning (baseline), recalling these individually learned sequences after a brief delay (recall), copying a novel sequence following a demonstration (novel imitation), and copying a familiar sequence that had been previously learned by trial and error (familiar imitation). Experiment 2 (n = 99) measured novel imitation and individual recall in addition to children’s ability to learn different sequences from a model’s mistake (goal emulation) and from physical/symbolic feedback provided automatically by a tablet (i.e., ghost condition). Results showed that familiar imitation and goal emulation developed early across tasks. Whereas novel imitation and ghost (affordance) learning developed late. An exploration of the dimensionality of these skills showed that imitation (Exp. 1), whether familiar or novel, was domain-specific. In contrast, emulation (Exp. 2) was multi-dimensional in the Spatial Task but unidimensional in the Cognitive Task. These results highlight the mosaic nature of children’s SL development. Results provide a model for explaining some of the observed variation in children’s performance across task and research paradigms. This information can be used to better predict when and why children are likely to succeed (or fail) in SL tasks. •3–6 years learned what (apple→Boy→Cat) and where (Top→Bottom→Right) sequences in two tablet-based tasks.•Sequences could be learned by individual recall, novel or familiar imitation, goal emulation or affordance learning (ghost control).•Familiar imitation and goal emulation developed early across tasks. Novel imitation and ghost (affordance) learning developed late.•There were few associations between learning conditions; Mostly restricted to within-task performance.•Results suggest that variation in social learning may be explained by domain-type and content-familiarity.